B-Cell-Mediated Strategies to Fight Chronic Allograft Rejection - Dalloul, Ali H. (Frontiers in Immunology, 2013)
Solid organs have been transplanted for decades. Since the improvement in graft selection and in medical and surgical procedures, the likelihood of graft function after one year is now close to 90%. Nonetheless even well-matched recipients continue to need medications for the rest of their lives hence adverse side effects and enhanced morbidity. Understanding Immune rejection mechanisms, is of increasing importance since the greater use of living-unrelated donors and genetically unmatched individuals. Chronic rejection is devoted to T-cells, however the role of B-cells in rejection has been appreciated recently by the observation that B-cell depletion improve graft survival. By contrast however, B-cells can be beneficial to the grafted tissue. This protective effect is secondary to either the secretion of protective antibodies or the induction of B-cells that restrain excessive inflammatory responses, chiefly by local provision of IL-10, or inhibit effector T-cells by direct cellular interactions. As a proof of concept B-cell-mediated infectious transplantation tolerance could be achieved in animal models, and evidence emerged that the presence of such B-cells in transplanted patients correlate with a favorable outcome. Among these populations, regulatory B-cells constitute a recently described population. These cells may develop as a feedback mechanism to prevent uncontrolled reactivity to antigens and inflammatory stimuli. The difficult task for the clinician, is to quantify the respective ratios and functions of “tolerant” vs effector B-cells within a transplanted organ, at a given time point in order to modulate B-cell-directed therapy. Several receptors at the B-cell membrane as well as signaling molecules, can now be targeted for this purpose. Understanding the temporal expansion of regulatory B-cells in grafted patients and the stimuli that activate them will help in the future to implement specific strategies aimed at fighting chronic allograft rejection.